LEGAL ANALYSIS OF THE CONSEQUENCES OF THE IMPLEMENTATION OF A SURROGACY CONTRACT BY A SURROGATE MOTHER ON THE STATUS OF INHERITANCE RIGHTS OF CHILDREN BORN IS REVIEWED FROM A POSITIVE LEGAL PERSPECTIVE - R. Febrina Andarina Zaharnika (International Conference On Law And Social Sciences, 2024)
Surrogacy Contract made by Surrogate Mother "Surrogate Mother" is a surrogate mother is an agreement between a woman who binds herself through an agreement with another party (husband and wife) to become pregnant with the results of the husband and wife's fertilization implanted into her womb, and after giving birth is required to hand over the baby to the husband and wife based on the agreement made. The purpose of this research study can formulate the main problems, namely first, How the analysis of the legal consequences of the implementation of the surrogacy contract by the surrogate mother on the inheritance status of the child born is reviewed based on a positive legal perspective, second, how the status of inheritance rights of children born from a surrogacy contract by a surrogate mother is reviewed based on a positive legal perspective. The research method is juridical normative using primary, secondary and tertiary legal materials. And the results of this research study, first, on the Surrogacy Contract by surrogate mother, the agreement is invalid under Article 1320 of the Civil Code because it does not meet the objective legal requirements in the agreement and is contrary to existing laws and regulations. Second, against the Surrogacy Contract by the surrogate mother of the inheritance rights of children born according to the Marriage Law, the child has the right to inherit from the surrogate mother's legal husband and his family.